Inclusive Education from the Contributions in the Virtual Forums of the Students of the Degree of Pedagogy at the University of Malaga - Mañas-Olmo, Moisés; González-Alba, Blas; Cortés-González, Pablo; Landin, Jeanette (International Federation of Engineering Education Societies, 2024)
The study of inclusive education (IE) today has a large body of international research that provides insights into the changes and strategies needed to make it a reality. However, we are witnessing the fact that educational and social changes are happening very slowly. We must continue to engage and delve into the judgments and opinions of the individuals who will make it achievable. We conducted a descriptive, analytical, and qualitative study to analyze the contributions of students in the virtual forums of five subjects over three academic years (2019–2020, 2020–2021, 2021–2022) in the pedagogy degree program (1st and 4th year). The study aimed to gather evidence of students’ commitment, involvement, learning, and knowledge construction in the context of IE. On the one hand, we have found evidence that students’ perceptions of IE are influenced by barriers and facilitators that either enable or restrict the progress of IE. On the other hand, we also present evidence of the level of engagement, reflection, and dedication of the students who have taken part in the online forums of the courses, as well as the knowledge they have gained through their participation. We recognize virtual forums as a space for students to meet, reflect, and collaboratively construct knowledge. It is a valuable tool for gaining insight into how students develop their perceptions, opinions, and learning.
Keywords: Educación inclusiva; Student participation; Pedagogy; Computer-aided learning; University studies; Education technology